Relationship Between Knowledge and Attitude of Breastfeeding Mothers in Providing Exclusive Breastfeeding at Pattingaloang Health Center - Asmirah, Rika; Rahmawati, Rahmawati (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
The first thousand days of life are a golden period that greatly determines the optimal growth and development of children. Exclusive breastfeeding plays an important role in meeting the nutritional needs of infants and reducing morbidity and mortality rates in children. However, the coverage of exclusive breastfeeding has not yet reached the expected target. Various factors, including the level of knowledge and attitude of mothers, are thought to influence the success of exclusive breastfeeding. This study aims to analyze the factors that influence exclusive breastfeeding in infants over 6 months of age in the Pattingaloang Health Center work area, South Sulawesi. This study used a correlation analytic design with a cross-sectional approach. The sample in this study were 33 mothers who had infants aged 6–24 months and were selected using the total sampling technique. Data were obtained through questionnaires and analyzed using the Chi-square test with the help of SPSS. The results of the analysis showed that there was a significant relationship between the level of maternal knowledge and exclusive breastfeeding (p-value = 0.028). Mothers with good knowledge are more likely to provide exclusive breastfeeding than mothers with poor knowledge. Meanwhile, no significant relationship was found between the mother's attitude towards breastfeeding and exclusive breastfeeding (p-value = 0.532). In addition, age, education level, and occupation also contribute to the formation of maternal knowledge about exclusive breastfeeding. The level of maternal knowledge significantly influences the success of exclusive breastfeeding, while maternal attitudes do not show a significant relationship. Therefore, efforts are needed to increase education and counseling regarding the importance of exclusive breastfeeding, especially for mothers with low education levels or limited access to health information